How to cope with stress: Elucidating mRNP packaging by the characterization of stress induced mRNPs - Seidler, Johanna Franziska; Justus Liebig University Giessen (My University, 2022)
In eukaryotic cells, transcription and translation are spatially separated and take place in the nucleus and the cytoplasm, respectively. Therefore, the transcribed messenger RNA (mRNA) needs to be exported from the nucleus for subsequent translation. Already during transcription mRNA-binding proteins are recruited and package the mRNA into a messenger ribonucleoprotein particle (mRNP). Only correctly processed and packaged mRNA will be exported through the nuclear pore complex into the cytoplasm. Although many components of the a nuclear mRNP are known (eg. Hpr1, Yra1, Nab2), the exact composition and structure remains unknown. During exposure to heat stress, Saccharomyces cerevisiae accumulates bulk mRNA within the nucleus, whereas heat shock mRNAs are exported. Until today it is not precisely known how these stress reactions are mediated. However, the dissociation of known mRNA export adaptors from the RNA seems to be a key feature. The aim of this study is the purification of a nuclear heat shock mRNP to elucidate mRNP composition and structure. For this purpose, a two-step purification strategy was applied, in which enrichment of all nuclear mRNPs by purification of the nuclear cap-binding complex was followed by a subsequent RNA purification step to enrich transcript-specific nuclear mRNPs. The purification of RNA was performed with an antisense oligonucleotide or different aptamer-based approaches. Even though the purification methods yielded a high enrichment of nuclear mRNPs containing the highly transcribed CCW12 mRNA, this was not the case for the purification of the heat shock mRNP containing SSA4 mRNA. In future studies, the focus for heat shock mRNPs will be shifted to the identification of the proteins forming the heat shock mRNP. Heat stress causes the accumulation of bulk mRNA within the nucleus. The second aim of this study is to investigate if this accumulation of poly(A)-RNA is a common stress reaction and how the cell mediates the nuclear mRNA export block. A nuclear poly(A)-RNA accumulation was not observed for all tested stresses. A previous study showed that the kinase Slt2 is essential for the mRNA export block during stress [Carmody et al., 2010]. However, no direct correlation between activation of Slt2 and the accumulation of mRNA for the different stresses tested could be observed in this study. In this work, a comparative phosphoproteome analysis was carried out to identify differential phosphorylation of known nuclear mRNA-binding proteins in a slt2 mutant. Deletion of SLT2 led to differentially phosphorylation of many proteins linked to mRNA export. Phosphorylation site mutants of nuclear mRNP components revealed that preventing phosphorylation of the Yra1 and Nab2 reduces the nuclear mRNA retention while a phosphomimicry mutant of Hpr1 increases nuclear poly(A)-RNA accumulation upon heat stress. Further studies are needed to understand by which mechanism the different mutants alter mRNA accumulation and how exactly the mRNA export block is mediated.
Keywords: ddc:570